Treatment for glioblastoma multiforme: current guidelines and Canadian practice - Ghose, A. (Multimed Inc., 2010)
PURPOSE: Our survey aimed to document variability in the practice patterns of Canadian radiation oncologists treating high-grade brain tumours. MATERIALS AND METHODS: A 20-question survey was developed to address various aspects of treatment: Guidelines used. Types of fusion protocols used. Number of treatment phases. Margins for volume delineation. Dose constraints. The survey was sent to Canadian radiation oncologists currently treating the central nervous system (cns) as one of their primary sites. RESULTS: We attained a 56% response rate from radiation oncologists across Canada treating cns sites. In their practice, 14% of respondents reported following guidelines from the European Organisation for Research and Treatment of Cancer; 32%, from the Radiation Therapy Oncology Group; and 56%, centre-specific guidelines. Single-phase treatment was reported by 60% of clinicians, and two-phase or multi-phase treatments, by 37%. For clinicians treating in single phase, margins from the gross treatment volume (gtv) to the planning treatment volume (ptv) included 0.5 cm (6%), 1 cm (6%), 1.5 cm (25%), 2.0 cm (56%), 2.5 cm (25%), and 3 cm (12.5%), with some respondents selecting more than one standard margin. For clinicians treating in multiple phases, margins from gtv to ptv in phase 2 included 1 cm (10%), 2.0 cm (40%), 2.5 cm (30%), and 3.0 cm (20%). Variability was also observed in dose constraints to critical structures. All respondents trimmed their margins to bony structures. CONCLUSIONS: Our survey shows considerable variation in the current treatment by Canadian radiation oncologists of high-grade brain tumours, especially with respect to guidelines followed, number of phases, and overall volume treated. Further studies are thus required to establish the evidence for optimal radiation volumes and phases, especially as brain tumour treatments evolve in the age of mr imaging and chemotherapy.